An Analysis and Research on the Transmission Ratio of Dye Sensitized Solar Cell Photoelectrodes by Using Different Etching Process - Chin-Guo Kuo; Cheng-Fu Yang; Mu-Jung Kao; Wen-Pin Weng; Chi-Cheng Chang; Lih-Ren Hwang; Jian-Lan Nil (International Journal of Photoenergy, 2013)
Classical photoelectrodes for Dye Sensitized Solar Cells (DSSCs) were fabricated by using the electrochemical method on the titanium (Ti) template, for that the fabrication process would influence the characteristics of the DSSCs. In this study, at first three different methods were used to etch Ti templates from 10 to 17 min, (1) polishing-chemical etching: Ti template was annealed at 450°C for 1 h, abraded using number 80 to 1500 SiC sheet, and then etched in a solution of 5% HF + 95% H2O; (2) electrochemical polishing-chemical etching: Ti template was annealed at 450°C for 1 h, electrolytic polishing with 42% CH3OH + 5% HClO4 + 53% HOCH2CH2OC4H9 solution, and the chemical-etching in a solution of 5% HF + 95% H2O; (3) chemical etching: Ti template was etched in a solution of 5% HF + 95% H2O and annealed at 450°C for 1 h. When the etching time was changed from 10 to 17 min, the thicknesses of Ti templates decreased from 75.3 μm to 14.8 μm, depending on the etching method. After etching process, the TiO2 nanotube arrays were fabricated as the photoelectrode of DSSCs by electrochemical process, in which the Ti as anode and platinum (Pt) as cathode. The electrolyte solution included C2H4(OH)2, NH4F, and deionized water. After annealing the grown TiO2 nanotube arrays at 450°C for 3 h, we would show that the etching process had large effect on the structure and transmittance ratio of the TiO2 nanotube arrays.